Developing pathways for oral care in elders: challenges in care for the dentate the subject?. (February 2014) - Walls, Angus
Abstract : Objective: This paper reviews potential age‐associated risk factors for satisfactory oral function and oral disease to inform the development of care pathways for the older person. Background: Alterations in dental status or both physical and biological change associated with age can impact on oral disease and oral function. Materials and Methods: Older people tend to have fewer teeth and some are edentulous. Physical and biological changes in bodily function with age can also affect oral health care either directly or indirectly. Results: Reductions in chewing ability impact on the foods people choose to eat because of perceived difficulty with chewing, with a potentially deleterious affect on dietary quality. This is worse in people with xerostomia where chewing and swallowing are impaired anyway. Change in the cell‐mediated inflammatory response impacts on gingival and periodontal disease manifestation and progression. Sarcopenia makes the physical act of toothbrushing more challenging. Caries remains a clinical problem that affects both the crowns and the roots of teeth. Coronal lesions tend to be around existing restorations where there is no evidence base about care/prevention. Conclusion: The physical and clinical changes that occur with ageing require an altered pattern of care for older people which is adjusted to their disease risk and encourage diversity of foods consumption.